Lessons from the MAI (UN New YorkUS, 1999)
Considers the factors that contributed to the decision of the members of the Organisation for Economic Coooperation and Development to discontinue the negotiations on the Multilateral Agreement on Investment. Draws lessons that could be of use for future negotiations of international investment agreements.
Keywords: INTERNATIONAL INVESTMENT